Microbial population inhibition method through spectrophotometry absorption of visible light applied to ecotoxicological analyses - Mainardi, Pedro Henrique [UNESP]; Bidoia, Ederio Dino [UNESP] (Macrothink Institute, 2020)
Ecotoxicology is a science that studies the effects of pollutants and forecast their transformations on the environment. Ecotoxicological studies have been used in soil and water quality assessment, development and implementation of new techniques of water and effluent treatment, tools for better industrial management, bioremediation techniques and sustainable agriculture approaches. Microorganisms, which were seen to detain a fundamental importance in nutrient cycling and energy flow, have been increasingly used as bioindicators in ecotoxicological analyses. The populational inhibition of microbiological strains may be measured through the absorbance of visible light, an efficient, fast, low-cost and reliable method that has been widely used in qualitative and quantitative analysis. In this manuscript, a real textile effluent sample was analyzed regarding its electric conductivity, pH, turbidity, solids, alkalinity, biochemical oxygen demand (BOD5), chemical oxygen demand (COD) and a spectrophotometry microbial population inhibition (MPI) method using the Bacillus subtilis bacteria and the Saccharomyces cerevisiae yeast. The EC20, EC50 and acute toxicity indexes were satisfactory in relation to the widely used method of light reduction of the Vibrio fischeri luminescence bacteria. The MPI was shown to be a feasible method to determine the hazardous effects caused by the textile effluent sample towards the microbial populations.
Keywords: Biosensors; Waste products; Landscape assessment